2019
DOI: 10.1111/1759-7714.13010
|View full text |Cite
|
Sign up to set email alerts
|

Curative effect assessment of immunotherapy for non‐small cell lung cancer: The “blind area” of Immune Response Evaluation Criteria in Solid Tumors (iRECIST)

Abstract: Background Immunotherapy has considerably changed the treatment of lung cancer. As immunotherapy has a special mechanism of action, the disease remission that it can induce is unique. Recently, Immune Response Evaluation Criteria in Solid Tumors (iRECIST), which focus on assessing the apparent curative effect of immunotherapy, have become widely accepted. Based on iRECIST criteria, if the response to immunotherapy is determined to be immunity‐confirmed progressive disease or immunity‐unconfirmed pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…An explanation might be that mixed PP&TPD-patients could have had a slowly developing and/or resolving pseudoprogression of lesions that were still classified as PD at 6 months. Some studies described continued benefit from immunotherapy, despite confirmed progression according to iRECIST criteria (40)(41)(42)(43). It could therefore be possible that some lesions that were defined as confirmed progression in our analysis may respond much later during treatment, as these delayed tumor response dynamics have been described for both melanoma and NSCLC patients by Nishino et al (43,44) and Hodi et al (39).…”
Section: Incidence Of Pseudoprogressionmentioning
confidence: 73%
“…An explanation might be that mixed PP&TPD-patients could have had a slowly developing and/or resolving pseudoprogression of lesions that were still classified as PD at 6 months. Some studies described continued benefit from immunotherapy, despite confirmed progression according to iRECIST criteria (40)(41)(42)(43). It could therefore be possible that some lesions that were defined as confirmed progression in our analysis may respond much later during treatment, as these delayed tumor response dynamics have been described for both melanoma and NSCLC patients by Nishino et al (43,44) and Hodi et al (39).…”
Section: Incidence Of Pseudoprogressionmentioning
confidence: 73%
“…The approach involves manually measuring changes in size of target lesions between baseline and follow-up CT scans in conjunction with RECIST guidelines (33,37). Unfortunately, pure morphological criteria, even with modifications and refinements (i.e., iRECIST), are not sufficient because they only provide a consistent standard for management of data collected in clinical trials rather than clinical practice or therapy decisions (35,(38)(39)(40)(41). Owing to its distinctive biologic mechanisms of action, immunotherapy can generate a tumor response pattern different from those found with cytotoxic chemotherapy or radiation therapy (42).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is a lack of standardized guidelines for assessing the efficacy of adjuvant therapy in lung adenocarcinoma. However, several scholars have argued that pathological assessment can effectively reflect clinical efficacy (23). After two cycles of treatment, the patient's response was assessed as stable disease, while postoperative pathology results confirmed the success of complete resection (R0).…”
Section: Discussionmentioning
confidence: 99%